Appropriate care of the newborn: ethical dilemmas - Dunn, P. M. (Journal of medical ethics, 1993)
Medical advances in newborn care have raised ethical dilemmas as to the level of care which is appropriate when an infant is severely damaged and incapable of a reasonable quality of life in the future. Some of the considerations, philosophical and practical, are discussed. It is concluded that within the framework of the law and after due consultation, decisions are best reached in privacy by the parents and their medical advisor and should be based on the perceived interests of the child.